Creating Places for People - Kirk, Mehron (project baikal, 2013)
The design of places has a huge impact on the success of urban areas. It has a role in helping develop a vision and identity within the built environment. Designing public spaces must be centred around the place - its physical characteristics, activities that happen within it, and the emotional reaction of a place. The success of places is governed by the perception of those who use it; we can influence this as designers and continue to create places where people want to live, work, learn and play.